Sensor-Polarimeter Based on Anisotropic Photonic Crystal for Solids and Liquids - Shmat'ko, A. A.; Odarenko, E. N.; Vertiy, A. A. (IEEE, 2020)
We solved the problem of determining the angle of polarization plane rotation for wave transmitted through anisotropic one-dimensional photonic crystal. Transfer matrix method is used to obtain analytical expressions for reflection and transmission coefficients of a plane wave of orthogonal polarizations for a limited number of photonic crystal periods. Crystalline quartz layers are used as anisotropic elements of photonic crystal. Effect of the gasoline permittivity varying that refers to octane number changing on the angle of polarization plane rotation is investigated.
Keywords: anisotropic photonic crystal; polarization plane rotating; permittivity; sensor-polarimeter